Evaluation of radiation shielding parameters for optical materials - Sayyed, M. I.; Lakshminarayana, Gandham; Mahdi, Mohd Adzir (National Institute of Materials Physics, National Institute of Optoelectronics, 2017)
In this work, we have evaluated the mass attenuation coefficient (μ/ρ), half value layer (HVL) and exposure buildup factors (EBF) for Bi-doped tellurite glass, and Dy-doped borate glass. The results show that the Bi-doped tellurite glass has higher μ/ρ and HVL than Dy-doped borate glass. These results could be useful in the construction of active shielding against hazardous gamma radiation.